Financing green development: 'Climate Bonds’ as a solution for institutional investors engagement - Aguiar, Paulo Ricardo Rua (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics